0359 The Moderating Role of Race in the Association of Adolescent Sleep Duration and Marijuana Use. (27th May 2020) - Levenson, J C; Atuahene, B; Bear, T; Hacker, K; Ricci, E; Goldstein, T R; Miller, E
Abstract: Introduction: Insufficient sleep and marijuana use during adolescence vary by race and are associated with poor outcomes in various domains. Sleep difficulties predict drug-related problems, but not all adolescents with insufficient sleep go on to use substances. We examined whether race/ethnicity moderates the association of sleep duration and marijuana use among Black/African-American and White adolescents using a countywide probability-based survey of adolescents. Methods: Using cross-sectional data (n=1447), logistic regression examined whether race moderated the association of adolescent sleep duration and recent marijuana use alone and after controlling for covariates in both weighted and unweighted models. Results: Hours of sleep was significantly negatively associated with recent marijuana use. Black/African-American youth in our sample had up to a 60% increased odds of marijuana use in the past 30 days compared to White youth, and they reported significantly shorter sleep duration than their White peers. In weighted models, Black/African-American youth had an increased probability of marijuana use with fewer hours of sleep as compared to White youth, even after accounting for covariates. Conclusion: In our countywide survey of adolescents, we found racial differences in the association of sleep duration and marijuana use. Future work should replicate our analyses with a longitudinal sample of adolescents to better evaluate the direction of these effects. Future efforts should also focus on identifying contextual factors that may explain racial differences in the sleep duration—substance use relationship, as well as developing strategies to reduce disparities in this relationship. Support: The Heinz Foundation, the Hillman Foundation, the Grable Foundation, and the FISA Foundation. Dr. Levenson's effort was supported by NICHD.